PENYELESAIAN SENGKETA WALI ADHOL DENGAN MEDIASI NON-LITIGASI OLEH PEGAWAI PENCATATAN NIKAH DI KUA KEDU - wardah hayya, yustika; Mujib, Mishbachul; Hidayat, Nabil Malik; Rifqiyanto, Agus Ilham; zumrotun, siti (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The aim of this research is to describe and analyze the non-litigation mediation process carried out by marriage registration officers at KUA Kedu in resolving guardian adhol dispute cases.  The research method uses a descriptive-qualitative approach which provides an overview of marriage problems related to guardian adhol and the role of the Kedu Religious Affairs Office (KUA) in resolving guardian adhol problems through non-litigation mediation. The data used is primary data sourced from field research. The data collection technique uses a direct observation approach and documentation. Data analysis uses narrative analysis which is analyzed using mediation theory, namely understanding conflict resolution effectively through communication and collaboration.  Research results on the role of KUA Kedu in resolving problems related to adhol guardians through non-litigation mediation attended by marriage guardians, prospective brides and grooms. The prospective bride's marriage guardian finally agreed to become the marriage guardian and carried out taukil wali bilkitabah (handing over the guardian's authority in writing) before the Head of the Kedu District KUA.  Keywords: Role, Resolving Adhol, Office of Religious Affairs